The effects of toy accessibility and organisation on student’s Play and teachers’ play engagement in a special education school in Iceland - Hildur María Arnalds 2001- (2024)
Naturalistic Teaching Methods are a collection of child-cantered methods using the child’s natural environment to create learning opportunities. The methods have been shown to be especially effective for autistic children with language difficulties and developmental disabilities in increasing language, communication and play skills. The incorporation of play is a key element in Naturalistic Teaching and therefore vital that teachers can successfully engage in play and the environment encourages play behaviour. In this study, I examined the effects of increased accessibility and organisation of toys on student’s play and teachers’ play engagement using a mixed between-within design. Participants included students and teachers in two classrooms (A and B) in a special education school in Iceland. Data was gathered through in-vivo observations. The analysis was done using independent t-tests, paired t-tests and Mann-Whitney U tests. Results between classrooms indicated that increased access and organisation of toys had immediate negative effect on students’ play and teachers’ play engagement but suggested the effects are not lasting. Results within classroom B showed increased accessibility and organisation of toys to have no effect. Keywords: Play, play engagement, toy accessibility, toy organisation, autism Náttúrulegar kennsluaðferðir eru samansafn aðferða sem hafa barnið í miðpunkti og nota umhverfi barnsins til þess að skapa tækifæri til náms. Sýnt hefur verið fram á að aðferðirnar séu sérstaklega áhrifaríkar til að auka tungumála-, samskipta- og leikfærni meðal einhverfra barna með tungumálaörðugleika og þroskahamlanir. Notkun leiks er lykilatriði í náttúrulegum kennsluaðferðum og því mikilvægt að kennarar geti tekið þátt í leik á árangursríkan hátt og að umhverfið ýti undir leikhegðun. Í þessari rannsókn skoðaði ég áhrifin sem aukið aðgengi og skipulag dóts hafði á leik nemenda og þátttöku kennara í leik. Ég notaði blendisnið fyrir innan- og milli hópa. Þátttakendur voru nemendur og kennarar í tveimur ...